Preparation method of wear-resistant super-hydrophobic coating with double covalent bonding interfaces

By constructing a dual covalent bonded interface in a superhydrophobic material, the problem of insufficient mechanical durability caused by weak interfacial bonding is solved, achieving a combination of wear resistance and superhydrophobicity. The coating maintains stability and functionality under harsh conditions.

CN121086648APending Publication Date: 2025-12-09SOUTHEAST UNIV
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202511360827.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-09-23
Publication Date
2025-12-09

AI Technical Summary

Technical Problem

Existing superhydrophobic materials lack mechanical durability, mainly due to the fragile interfacial bonding, which makes the micro-nano structures easily damaged under friction, scratching or fluid impact, thus losing their superhydrophobic function.

Method used

By constructing a first chemical bonding interface between micro- and nano-structures and forming a second covalent bonding interface between the micro- and nano-structures and the polymer matrix, stable urethane covalent bonds are formed by utilizing the covalent bonding between halloysite nanotubes and nano-silica, combined with the nucleophilic addition reaction of waterborne polyurethane resin, thus achieving a strong connection between particles and the matrix.

Benefits of technology

The prepared coating maintains good mechanical durability and superhydrophobicity under harsh working conditions, and can still maintain a contact angle of 150.2° after 1500 Taber abrasion cycles. It also has excellent self-cleaning ability, chemical stability, and acid and alkali resistance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN121086648A_ABST
    Figure CN121086648A_ABST
Patent Text Reader

Abstract

The invention discloses a preparation method of a wear-resistant super-hydrophobic coating with double covalent bonding interfaces, which comprises the following steps: (1) sequentially adding deionized water, ammonia water and halloysite into absolute ethyl alcohol, continuously stirring under a water bath condition, then slowly dropwise adding tetraethoxysilane into the mixture, keeping high-speed stirring, and cooling to room temperature; nano silicon dioxide particles are generated on the surface of the halloysite in situ, and HNTs-SiO2 micro-nano particles are formed; (2) slowly dropwise adding a low-surface-energy substance into the mixed solution in which the micro-nano particles are generated in the step (1), and continuously stirring in a water bath to obtain a super-hydrophobic suspension; collecting precipitates after solid-liquid separation, and then drying, grinding and screening to obtain super-hydrophobic composite particles; and (3) dispersing waterborne polyurethane resin and the super-hydrophobic composite particles in the step (2) in deionized water containing a nonionic surfactant, uniformly mixing to obtain a coating, spraying the obtained coating on the surface of a substrate, and curing to obtain the wear-resistant super-hydrophobic coating.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to a method for preparing a wear-resistant superhydrophobic coating with a dual covalent bonded interface. Background Technology

[0002] Superhydrophobic surface engineering is a cutting-edge branch of functional materials, endowing materials with excellent properties such as self-cleaning, corrosion resistance, and anti-icing, demonstrating enormous application potential in key fields such as aerospace, marine engineering, and energy and power. The superhydrophobicity of superhydrophobic materials relies on the synergistic effect of two key factors: firstly, the low surface energy chemistry of the material surface; and secondly, the layered rough structure combining micron and nanoscale components. This structure can capture and stabilize an air cushion, forming a Cassie-Baxter wetting state, allowing water droplets to suspend on it, thereby achieving an extremely high water contact angle (greater than 150°) and an extremely low roll-off angle (less than 10°).

[0003] Despite significant advancements in the fabrication methods of existing superhydrophobic materials, their practical applications remain hampered by a core bottleneck: severely insufficient mechanical durability. The fundamental reason lies in the inherent fragility of the intricate micro / nano structures upon which superhydrophobicity depends. Under mechanical stresses such as friction, scratching, or fluid impact, these structures are highly susceptible to physical damage or detachment from the substrate. This leads to the loss of stable support for the air cushion, an irreversible transformation of the surface from a low-adhesion Cassie-Baxter state to a high-adhesion Wenzel wetting state, and ultimately, the complete loss of superhydrophobic functionality.

[0004] A thorough analysis of the failure mechanism reveals that the root cause of insufficient mechanical durability lies in the fragility of the interfacial bonding. Most existing technologies employ physical blending methods, dispersing pre-prepared functional particles (such as SiO2) within a polymer binder. In such systems, the functional particles and the polymer matrix, as well as the micron and nanoparticles constituting the hierarchical structure, are primarily bound by weak van der Waals forces or physical entanglement. These weak, non-chemically bonded interfaces cannot effectively transfer and disperse stress under shear stress, causing functional particles to easily "pull out" or detach from the matrix, leading to "disintegration" failure of the coating structure. Therefore, improving the overall connectivity of the coating system's internal structure is crucial for solving this problem. Summary of the Invention

[0005] Purpose of the invention: The purpose of this invention is to provide a method for preparing a wear-resistant superhydrophobic coating with a dual covalent bond interface. This method constructs a first chemical bond interface between micro- and nano-structures and forms a second covalent bond interface between the micro- and nano-structures and the polymer matrix, thereby fundamentally solving the problem of insufficient interfacial bonding force. This allows the superhydrophobic coating to maintain good intrinsic mechanical durability and long-term hydrophobicity even under harsh working conditions.

[0006] Technical solution: The method for preparing the wear-resistant superhydrophobic coating of the present invention includes the following steps:

[0007] (1) Add small amounts of deionized water (the main purpose of adding deionized water is to promote the hydrolysis-condensation reaction of low surface energy substances, so that they form stable Si-O-Si chemical bonds on the particle surface, thereby achieving long-lasting superhydrophobic modification), ammonia, and halloysite (HNTs) sequentially to anhydrous ethanol. Stir continuously under water bath conditions, and then slowly add tetraethyl orthosilicate (TEOS) dropwise at a rate of 0.2-1.0 mL / min, preferably at a rate of 0.5 mL / min. The purpose of slow dropwise addition is to control the hydrolysis-condensation rate of TEOS and avoid local over-addition. Saturation and agglomeration are ensured to achieve uniform nucleation of particles. High-speed stirring at 1000 r / min is maintained (high-speed stirring can prevent local concentration gradients and temperature gradients, and avoid SiO2 from agglomerating too quickly in a certain area; strong mixing helps to disperse newly generated SiO2 nucleation points, inhibit particle agglomeration, and promote uniform particle growth), so that nano-silica particles are generated in situ on the surface of halloysite, forming HNTs-SiO2 micro-nano particles; the key process parameters in step (1) are to control the amount and rate of TEOS addition, and to ensure uniform nucleation of nanoparticles while controlling the particle size of nanoparticles.

[0008] (2) Slowly add a low surface energy substance to the mixed solution after generating micro-nano particles in step (1), and continue to stir magnetically in a water bath to obtain a superhydrophobic suspension; after standing and separating into layers, pour off the supernatant, collect the precipitate, dry it, grind and sieve it to obtain superhydrophobic composite particles.

[0009] (3) Disperse the waterborne polyurethane resin and the superhydrophobic composite particles from step (2) in deionized water containing a nonionic surfactant. After mixing evenly, a coating is obtained. The coating is sprayed onto the substrate surface and cured to obtain a wear-resistant superhydrophobic coating.

[0010] Step (1) is used to construct the first covalent bonding interface. Halloysite nanotubes with active hydroxyl groups on their surface are selected as micron-scale reactive frameworks. In an ethanol-ammonia-water system, tetraethyl orthosilicate (TEOS) is hydrolyzed and condensed in situ using a sol-gel method. The resulting silica nanoparticles form Si-O-Al or Si-O-Si covalent bonds with the active hydroxyl groups on the surface of the halloysite nanotubes through a dehydration condensation reaction, thereby obtaining micro-nano hierarchical composite particles with a permanently bonded nano-rough structure on the surface. In step (1), the halloysite has a hollow tubular structure with a pore size of 15-20 nm and a tube length of 5-20 μm. The nano-silica contains silica nanoparticles formed by the in-situ hydrolysis and condensation reaction of tetraethyl orthosilicate (TEOS), and the particle size of the silica nanoparticles is 100-200 nm. The mass ratio of halloysite to tetraethyl orthosilicate is 6:5; the water bath reaction temperature is 45–55℃, and the reaction time is 6–8 h.

[0011] Step (2) involves surface chemical modification of the micro / nano hierarchical composite particles obtained in step (1). By controlling the reaction conditions, the fluorosilane low surface energy modifier reacts only with some of the hydroxyl groups on the surface of the micro / nano hierarchical composite particles, imparting hydrophobicity while retaining sufficient unreacted hydroxyl groups as active sites for subsequent reactions. In step (2), the low surface energy substance is one of perfluorodecyltriethoxysilane, perfluorooctyltriethoxysilane, or perfluorodecyltrichlorosilane; the amount of low surface energy substance added is 16-17% of the amount of halloysite added; the water bath reaction temperature is 45-55℃, and the reaction time is 6-8h.

[0012] Superhydrophobic composite particles with HNTs as the core, SiO2 grown in situ on the surface and grafted with fluorinated silanes, and meeting at least one of the following characteristics, are considered successfully modified: (i) the atomic fraction of fluorine (F) on the surface as detected by XPS is ≥8%; (ii) the weight loss rate of TGA in the temperature range of 300–400 °C is 20%–40%; (iii) the weight loss rate of FTIR in the temperature range of 1200–1230 cm⁻¹ is ≥8%. -1 The characteristic absorption peak of -CFx appears, and it is located between 3200 and 3600 cm⁻¹. -1 The -OH peak in the region was significantly weakened compared to before modification; (iv) after the superhydrophobic composite particles were placed in deionized water and left to stand for 90 days, they still all floated on the water surface.

[0013] Step (3) is used to construct the second covalent bonding interface. The superhydrophobic composite particles with active hydroxyl groups on their surface obtained in step (2) are dispersed in an aqueous polyurethane resin matrix. A nucleophilic addition reaction is initiated by thermosetting, so that the active hydroxyl groups retained on the surface of the superhydrophobic composite particles react with the isocyanate groups (-NCO) in the aqueous polyurethane resin system to form urethane covalent bonds, thereby chemically anchoring the entire micro-nano hierarchical composite particle unit in the polymer network. In step (3), the mass ratio of superhydrophobic composite particles to aqueous polyurethane resin is 1.5 to 3.5:5, more preferably 2.6:5; the deionized water contains 0.1% to 0.3% of nonionic surfactants in the total mass of the solution (the total mass of solvent plus nonionic surfactants); the nonionic surfactants are selected from at least one of alkylphenol polyoxyethylene ether nonionic surfactants, fatty alcohol polyoxyethylene ether nonionic surfactants, and polyoxyethylene-polyoxypropylene block copolymer nonionic surfactants.

[0014] In step (3), the substrate is placed on a hot table at 120℃~170℃, and the coating is sprayed onto the surface of the substrate to prepare a coating; the curing temperature is 100~150℃, and the curing time is not less than 4h; the thickness of the wear-resistant superhydrophobic coating obtained by the present invention is 10~80μm, preferably 20~60μm.

[0015] HNTs, an aluminosilicate clay mineral, are rich in highly reactive aluminum hydroxyl (Al-OH) and silanol (Si-OH) groups on their inner and outer surfaces. These hydroxyl groups provide natural anchoring sites for subsequent chemical reactions. Using the sol-gel method, under ammonia catalysis, the silanol groups (Si-OH) generated by the hydrolysis of TEOS undergo a dehydration condensation reaction with the active hydroxyl groups on the HNTs surface, forming extremely stable Si-O-Al and Si-O-Si covalent bonds. This process enables the in-situ growth and covalent grafting of nano-silica particles onto the HNTs surface, constructing chemically bonded, structurally stable micro-nano hierarchical composite particles. When hydrophobically modifying HNTs-SiO2 composite particles, this invention precisely controls the reaction conditions so that the fluorinated silane reacts only with a portion of the surface hydroxyl groups. This ensures that the modified composite particles retain significant hydroxyl absorption peaks. These retained residual hydroxyl groups become the key "chemical hooks" connecting the composite particles to the polymer matrix. The superhydrophobic composite particles with chemical hooks on their surface, prepared above, are dispersed in an aqueous polyurethane resin matrix. During the final coating curing process, these -OH groups undergo nucleophilic addition reactions with isocyanate groups (-NCO) in the aqueous polyurethane (WPU) system to form high-strength urethane covalent bonds. This chemically anchors the entire micro-nano hierarchical composite particle unit to the polymer network, enabling the micro-nano hierarchical composite particles to be "welded" to the polymer matrix network through chemical bonds. The functional filler particles are no longer independent phases dispersed in the polymer, but become part of the entire three-dimensional network structure.

[0016] Beneficial effects: Compared with the prior art, the present invention has the following significant advantages:

[0017] (1) The coating prepared by the present invention has a double covalent bond interface. The double covalent bond within the particles and between the particles and the matrix can effectively suppress the damage and peeling of the micro-nano structure during the wear process. After the coating is worn for 1500 cycles under a 1kg heavy load in a Taber abrasion tester, the wear rate is only 33.2%, and the wear area still maintains a contact angle of 150.2°, maintaining a superhydrophobic state. Therefore, the coating has good mechanical durability and superhydrophobic stability.

[0018] (2) This invention replaces physical adsorption in traditional technology with chemical bonding. The first covalent bonding interface ensures the stability of the nano-roughness structure unit; the second covalent bonding interface firmly anchors the entire functional filler unit in the polymer matrix, fundamentally eliminating weak links at the interface. Good interfacial bonding is the core guarantee for the high wear resistance of the coating.

[0019] (3) The coating is not only wear-resistant, but its stable Cassie-Baxter state also gives it excellent self-cleaning ability. Water droplets can roll off and remove contaminants, keeping the surface clean. At the same time, the coating can still maintain superhydrophobicity after being soaked in strong acid (pH=2) and strong alkali (pH=12) environments, showing excellent chemical stability. Attached Figure Description

[0020] Figure 1 The images show scanning electron microscope (SEM) images of nanolayered structures formed on the particle surface after TEOS hydrolysis; a and b are the smooth surfaces of the original HNTs; c and d are the nano-SiO2 layers uniformly covering the surface of HNTs after in-situ TEOS reaction. The silanol groups (Si-OH) generated by TEOS hydrolysis undergo dehydration condensation with the active hydroxyl groups on the HNTs surface to form extremely stable Si-O-Al and Si-O-Si covalent bonds; e and f are the surfaces of carbon fibers after in-situ TEOS reaction. The carbon fibers have a stable chemical structure, no hydroxyl sites on the surface, and SiO2 exhibits non-uniform physical adsorption.

[0021] Figure 2 The image shows the dispersion state of the modified superhydrophobic halloysite powder in water. After standing at room temperature for 90 days, the powder still floats on the water surface, demonstrating its excellent and long-lasting hydrophobicity. a is the initial dispersion state; b is the dispersion state of the powder after standing at room temperature for 90 days.

[0022] Figure 3 The coatings are denoted by: a) coating of Example 1 (WCA 153.2°, SA 5°); b) coating of Comparative Example 1 (WCA 148°, SA 15°).

[0023] Figure 4 The images show the Fourier transform infrared (FTIR) spectra of the two micro / nano hierarchical composite particles in Example 1 and Comparative Example 1 before and after hydrophobic modification; a) shows the micro / nano hierarchical composite particles of Example 1 after hydrophobic modification, displayed at 1200 cm⁻¹. -1 ~1300cm -1 -CFx peak and 3200cm -1 ~3600cm -1 The retained -OH peak; b is the hydrophobically modified micro-nano hierarchical composite particle of Comparative Example 1, where the -OH peak is not obvious (a small amount of nano-SiO2 was not grafted with fluorine-containing low surface energy material, thus retaining some -OH).

[0024] Figure 5 The X-ray photoelectron spectroscopy (XPS) spectra of halloysite in Example 1 and carbon fiber before and after hydrophobic modification in Comparative Example 1 are shown.

[0025] Figure 6Thermogravimetric (TGA) spectra of the two micro / nano hierarchical composite particles in Example 1 and Comparative Example 1 are shown.

[0026] Figure 7 The FTIR spectrum of the final coating ( Figure 7 The HNT-Pu-Coating in the sample showed the disappearance of the -OH peak, confirming the achievement of a second chemical bond.

[0027] Figure 8 This is a graph showing the changes in pore structure parameters of HNTs before and after TEOS hydrolysis in Example 1;

[0028] Figure 9 The diagram shows the abrasion resistance test results; a is a schematic diagram of Taber abrasion; b shows the changes in the coating WCA and SA after 1500 abrasion cycles, proving its superior durability.

[0029] Figure 10 The SEM images of the coating before and after wear in Example 1 show that the micro-nano structure still exists after 1500 wear cycles, confirming the strength of the first chemical bond.

[0030] Figure 11 The SEM images of the coating before and after wear in Comparative Example 1 (carbon fiber based) show that the micro-nano particles completely detached after wear.

[0031] Figure 12 The diagram shows the wear of the coating in Comparative Example 2 (fluorocarbon resin-based), illustrating its rapid failure; the mass ratios of the resin matrix and composite particles are a: 5:2; b: 5:2.6; c: 5:3, respectively.

[0032] Figure 13 The FTIR spectrum of the coating formed in Comparative Example 2 is shown at 3200 cm⁻¹. -1 -3600cm -1 The -OH absorption peak in the infrared spectral region disappears;

[0033] Figure 14 The diagram shows the performance of the coating in Comparative Example 3 (epoxy resin-based), indicating that it is not superhydrophobic and has extremely poor wear resistance; where a is a schematic diagram of coating wettability; b is a schematic diagram of wear.

[0034] Figure 15 The image shows the dustproof and self-cleaning effect of the wear-resistant superhydrophobic coating prepared in Example 1.

[0035] Figure 16 The acid and alkali resistance of the wear-resistant superhydrophobic coating prepared in Example 1 is shown in Figure 1; a is an HCl solution (pH=2) and b is a NaOH solution (pH=12). Detailed Implementation

[0036] Example 1

[0037] The method for preparing the wear-resistant superhydrophobic coating of the present invention includes the following steps:

[0038] (1) Preparation of HNTs-SiO2 micro-nano hierarchical composite particles (first covalent bonding interface): 20 parts by mass of deionized water, 20 parts by mass of ammonia water and 12 parts by mass of halloysite (hollow tubular structure, 5-20 μm in length and 15-20 nm in pore size) were added sequentially to 200 parts by mass of anhydrous ethanol. Under the conditions of heating in a water bath at 45-55℃ and continuous high-speed stirring (≥1000 rpm), 10 parts by mass of TEOS (dropping rate of 0.5 mL / min) were slowly added dropwise. Under these reaction conditions, the silanol groups generated by the hydrolysis of TEOS covalently bonded to the hydroxyl groups on the surface of HNTs, and a layer of chemically grafted nano-SiO2 particles was generated in situ on the surface of HNTs. The reaction was continued for 6-8 hours to obtain HNTs-SiO2 micro-nano hierarchical composite particles.

[0039] (2) Hydrophobication and retention of active sites of HNTs-SiO2 micro-nano hierarchical composite particles: Keep the solution temperature at 45-55℃, slowly add 2 parts by mass of perfluorodecyltriethoxysilane to the above suspension, and continue magnetic stirring for 6-8 hours; In this step, the fluorinated silane reacts with some of the surface hydroxyl groups, giving the composite particles low surface energy, while retaining enough hydroxyl groups for subsequent reactions; After the reaction is completed, let it stand and separate into layers, pour off the supernatant, dry the precipitate in an oven at 100-150℃, grind it and pass it through a 200-mesh sieve to obtain superhydrophobic composite particles with active hydroxyl groups on the surface;

[0040] (3) Second covalent bonding interface: 5 parts by mass of waterborne polyurethane resin (WPU, Bayhydrol UH 2593) and 2.6 parts by mass of the superhydrophobic composite particles from step (2) are dispersed in 15 parts by mass of deionized water containing nonionic surfactant (1-3‰ of the total mass of the solution), and mixed and stirred evenly to obtain a coating; the coating is evenly sprayed onto the substrate using a spray gun, and then heat-cured at 100-150℃ for at least 4 hours; during the heat curing process, the remaining hydroxyl groups on the surface of the superhydrophobic composite particles react with the isocyanate groups in WPU to form urethane covalent bonds, which firmly anchor the superhydrophobic composite particles in the resin matrix to form a wear-resistant superhydrophobic coating with a thickness of about 50μm.

[0041] Figure 15 The specific experimental procedure was as follows: a layer of Fe3O4 powder was evenly sprinkled onto the wear-resistant superhydrophobic coating and the bare glass surface, and then water droplets were slowly released onto the surface using a dropper to observe the movement of the water droplets. Figure 15As can be seen, compared with bare glass, when water droplets roll off the wear-resistant superhydrophobic coating, they carry away the dust along their trajectory, and there are almost no water marks left, which proves that this coating has excellent dustproof and self-cleaning effects.

[0042] Comparative Example 1

[0043] A method for preparing a superhydrophobic coating includes the following steps:

[0044] (1) Add 20 parts by mass of deionized water, 20 parts by mass of ammonia and 12 parts by mass of carbon fiber to 200 parts by mass of anhydrous ethanol in sequence. Under the conditions of heating in a water bath at 45-55℃ and continuous high-speed stirring (≥1000rpm), slowly add 10 parts by mass of TEOS (dropping rate of 0.5mL / min). Under these reaction conditions, the silica nanoparticles formed by the in-situ hydrolysis and condensation reaction of tetraethyl orthosilicate (TEOS) are unevenly physically adsorbed on the carbon fiber. After the reaction continues for 6-8 hours, micro-nano hierarchical composite particles are obtained.

[0045] (2) Keep the solution temperature at 45-55℃, slowly add 2 parts by mass of perfluorodecyltriethoxysilane to the above suspension, and continue to stir magnetically for 6-8 hours; after the reaction is completed, let it stand to separate into layers, pour off the supernatant, dry the precipitate in an oven at 100-150℃, grind it and pass it through a 200-mesh sieve to obtain superhydrophobic composite particles.

[0046] (3) Disperse 5 parts by weight of waterborne polyurethane resin (WPU) and 2.6 parts by weight of the superhydrophobic composite particles from step (2) in 15 parts by weight of deionized water containing nonionic surfactant (1-3‰ of the total mass of the solution), mix and stir evenly to obtain a coating; use a spray gun to evenly spray the coating onto the substrate, and then heat cure at 100-150°C for at least 4 hours to obtain a superhydrophobic coating.

[0047] Due to the chemical inertness of carbon fiber surfaces and the absence of active hydroxyl groups, SiO2 nanoparticles can only physically adsorb onto their surface. Figure 1 e,f), resulting in poor wear resistance of the coating, which exposes the substrate in less than 500 wear cycles under a 1kg load, and the nanoparticles almost completely detach after wear. Figure 11 c, d), proves that the lack of the first covalent bonding interface is the root cause of its rapid wear failure. From Figure 5 As can be seen, the hydrophobically modified halloysite has a higher fluorine content than carbon fiber, meaning that more low surface energy materials are grafted onto the surface of halloysite; at the same time, from Figure 6 As can be seen, the weight loss rate of halloysite in Example 1 was 35.9%, while the weight loss rate of carbon fiber in Comparative Example 1 was 21.6%, demonstrating the successful grafting of low surface energy materials, and that the amount of low surface energy material grafted onto the halloysite surface was even higher. Figure 8It is known that the specific surface area of ​​the original halloysite nanotubes is 21.4425 m². 2 / g, pore volume is 0.086cm³ 3 / g, with a pore diameter of 16.042nm; after TEOS hydrolysis to generate nanoparticles, halloysite has a specific surface area of ​​7.5673m². 2 / g, pore volume 0.15cm³ 3 / g, with a pore diameter of 8.0679nm, indicates that the generated nanoparticles filled part of the pores, thus reducing the porosity of halloysite. The reduction in porosity can reduce stress concentration on the coating surface, thereby enhancing its mechanical wear resistance.

[0048] Comparative Example 2

[0049] A method for preparing a superhydrophobic coating includes the following steps:

[0050] (1) Add 20 parts by mass of deionized water, 20 parts by mass of ammonia water and 12 parts by mass of halloysite (hollow tubular structure, 5-20 μm long and 15-20 nm in diameter) to 200 parts by mass of anhydrous ethanol in sequence. Under the conditions of heating in a water bath at 45-55℃ and continuous high-speed stirring (≥1000 rpm), slowly add 10 parts by mass of TEOS (dropping rate of 0.5 mL / min). Under these reaction conditions, the silanol groups generated by the hydrolysis of TEOS covalently bond with the hydroxyl groups on the surface of HNTs, and generate a layer of chemically grafted nano-SiO2 particles in situ on the surface of HNTs. Continue the reaction for 6-8 hours to obtain HNTs-SiO2 micro-nano hierarchical composite particles.

[0051] (2) Keep the solution temperature at 45-55℃, slowly add 2 parts by mass of perfluorodecyltriethoxysilane to the above suspension, and continue to stir magnetically for 6-8 hours; after the reaction is completed, let it stand to separate into layers, pour off the supernatant, dry the precipitate in an oven at 100-150℃, grind it and pass it through a 200-mesh sieve to obtain superhydrophobic composite particles.

[0052] (3) Disperse 5 parts by weight of oily 41082 fluorocarbon resin and 2.6 parts by weight of the superhydrophobic composite particles from step (2) into 15 parts by weight of butyl acetate containing nonionic surfactant (1-3‰ of the total mass of the solution), mix and stir evenly to obtain a coating; use a spray gun to evenly spray the coating onto the substrate, and then heat cure at 100-150°C for at least 4 hours to obtain a superhydrophobic coating.

[0053] Coatings were also prepared simultaneously with 41082 fluorocarbon resin and superhydrophobic composite particles at mass ratios of 5:2 and 5:3. Although the coating prepared in Comparative Example 2 had good initial hydrophobicity, it exposed the substrate after 500 wear cycles under a relatively light load of 500g. Figure 12The wear resistance decreased rapidly and significantly, which proves that the WPU resin matrix selected in this invention has synergistic advantages in achieving the second covalent bonding interface and its own excellent mechanical properties.

[0054] Comparative Example 3

[0055] A method for preparing a superhydrophobic coating includes the following steps:

[0056] (1) Add 20 parts by mass of deionized water, 20 parts by mass of ammonia water and 12 parts by mass of halloysite (hollow tubular structure, 5-20 μm long and 15-20 nm in diameter) to 200 parts by mass of anhydrous ethanol in sequence. Under the conditions of heating in a water bath at 45-55℃ and continuous high-speed stirring (≥1000 rpm), slowly add 10 parts by mass of TEOS (dropping rate of 0.5 mL / min). Under these reaction conditions, the silanol groups generated by the hydrolysis of TEOS covalently bond with the hydroxyl groups on the surface of HNTs, and generate a layer of chemically grafted nano-SiO2 particles in situ on the surface of HNTs. Continue the reaction for 6-8 hours to obtain HNTs-SiO2 micro-nano hierarchical composite particles.

[0057] (2) Keep the solution temperature at 45-55℃, slowly add 2 parts by mass of perfluorodecyltriethoxysilane to the above suspension, and continue to stir magnetically for 6-8 hours; after the reaction is completed, let it stand to separate into layers, pour off the supernatant, dry the precipitate in an oven at 100-150℃, grind it and pass it through a 200-mesh sieve to obtain superhydrophobic composite particles.

[0058] (3) Disperse 5 parts by weight of oily epoxy resin and 2.6 parts by weight of the superhydrophobic composite particles from step (2) into 15 parts by weight of butyl acetate containing nonionic surfactant (1-3‰ of the total mass of the solution), mix and stir evenly to obtain a coating; use a spray gun to evenly spray the coating onto the substrate, and then heat cure at 100-150°C for at least 4 hours to obtain a superhydrophobic coating.

[0059] The resulting coating could not achieve a superhydrophobic state (WCA only 138°, high adhesion) and had extremely poor abrasion resistance, exposing the substrate in less than 30 wear cycles under a 500g load. Figure 14 ).

[0060] Comparative Example 4

[0061] A method for preparing a coating includes the following steps:

[0062] (1) Add 20 parts by mass of deionized water, 20 parts by mass of ammonia water and 12 parts by mass of halloysite (hollow tubular structure, 5-20 μm long and 15-20 nm in diameter) to 200 parts by mass of anhydrous ethanol in sequence, heat in a water bath at 45-55℃ and stir continuously at high speed (≥1000 rpm) for 6-8 hours to obtain a suspension;

[0063] (2) Keep the solution temperature at 45-55℃, slowly add 2 parts by mass of perfluorodecyltriethoxysilane to the above suspension, and continue to stir magnetically for 6-8 hours; after the reaction is completed, let it stand to separate into layers, pour off the supernatant, dry the precipitate in an oven at 100-150℃, grind it and pass it through a 200-mesh sieve to obtain superhydrophobic composite particles.

[0064] (3) Disperse 5 parts by weight of waterborne polyurethane resin (WPU) and 2.6 parts by weight of the superhydrophobic composite particles from step (2) in 15 parts by weight of deionized water containing nonionic surfactant (1-3‰ of the total mass of the solution), mix and stir evenly to obtain a coating; use a spray gun to evenly spray the coating onto the substrate, and then heat cure at 100-150°C for at least 4 hours to obtain a coating layer.

[0065] The coating obtained in Comparative Example 4 lacks superhydrophobicity at all, with a static water contact angle of approximately 105° and a roll-off angle greater than 90°, indicating that droplets are firmly pinned to the surface. Under a 500g load abrasion test, the coating is destroyed within 400 cycles, demonstrating poor abrasion resistance.

[0066] Comparative Example 5

[0067] Compared to Example 1, the only difference in Comparative Example 5 is that in step (2), when adding perfluorodecyltriethoxysilane, 2 parts by mass of perfluorodecyltriethoxysilane were directly poured into the suspension.

[0068] Comparative Example 6

[0069] Compared to Example 1, the only difference in Comparative Example 5 is that 15 parts by mass of TEOS were slowly added in step (1).

[0070]

[0071]

[0072] As shown in Table 1, the excellent wear resistance of Example 1 stems from the construction of the first covalent bonding interface. Halloysite (HNTs), due to its unique aluminosilicate chemical structure and surface rich in active hydroxyl groups, provides a "chemical anchor" for covalent grafting of silica generated by TEOS hydrolysis, thus forming a strong Si-O-Al / Si-O-Si chemical bond. In contrast, the carbon fiber surface in Comparative Example 1 is chemically inert and cannot form chemical bonds; silica can only be physically adsorbed through weak van der Waals forces, as evidenced by the wear test results (…). Figure 9 ) and SEM morphology after wear ( Figures 10-11This contrasts sharply with the coating of Example 1. In Example 1, the nanostructure remained stable after 1500 cycles of heavy-duty wear; while in Comparative Example 1, the physically adsorbed nanoparticles were easily peeled off, leading to rapid coating failure.

[0073] By precisely controlling the amount of low surface energy material added, sufficient active hydroxyl groups are retained on the surface of HNTs-SiO2 composite particles. Figure 4 (as confirmed by a) these hydroxyl groups react with isocyanate groups in the waterborne polyurethane (WPU) matrix to form strong urethane covalent bonds ( Figure 7 (Confirmation of the disappearance of the -OH peak) indicates that the composite particles are "welded" into the polymer network. Although the fluorocarbon resin of Comparative Example 2 has better initial hydrophobicity, its abrasion resistance is far inferior to that of Example 1 ( Figure 12 The epoxy resin system in Comparative Example 3 showed a complete performance collapse, being neither hydrophobic nor extremely abrasion-resistant. Figure 14 This proves that the second covalent bonding interface is the key to ensuring that the functional particles do not detach from the matrix, and that choosing a waterborne polyurethane matrix that can provide reactive functional groups and has excellent mechanical properties is a necessary condition for achieving the ultimate coating's superior durability.

[0074] The coating surface of Comparative Example 4 only has micron-sized tubular structures and lacks nanostructures, making it unable to effectively trap air pads and form a stable Cassie-Baxter state. The coating of Comparative Example 4 cannot achieve a superhydrophobic state at all (contact angle only ~105°), and droplets are firmly pinned to the surface, exhibiting extremely high adhesion. Its wear resistance is also extremely poor because the smooth tubular filler has weak bonding force with the substrate and lacks sacrificial nanostructures to resist wear.

[0075] In Comparative Example 5, when the addition rate of perfluorosilicone-based triethoxysilane was too fast, the fluorosilane could not be fully hydrolyzed, which significantly reduced the amount of fluorosilane grafted onto the particles, making the modified particles unable to be superhydrophobic. In Comparative Example 6, when the amount of TEOS added was too high, the particle size of the nanoparticles increased, resulting in increased coating roughness and droplet pinning adhesion. Excessive roughness also increased stress concentration, thereby reducing the wear resistance of the coating.

[0076] This invention utilizes two interfacial chemical bonds to "stitch" the nanostructure, micro-framework, and polymer matrix into a highly integrated organic-inorganic three-dimensional hybrid network: the Si–O–Al / Si–O–Si chemical bonds between HNTs / SiO2 enhance particle-particle bonding strength; residual -OH groups on the particle surface covalently / hydrogenally couple with resin segments to strengthen the particle-resin interface; and WPU provides toughness energy dissipation and crack passivation, achieving a hard-tough synergistic wear resistance, fundamentally improving the coating's cohesion and wear resistance. The coating prepared by this invention maintains its non-exposed and superhydrophobic state even under high contact angle (≥150°) and low roll-off angle (≤10°) conditions, after 1500 cycles of Taber 1kg heavy load, and exhibits excellent dustproof self-cleaning and acid / alkali media stability (remaining superhydrophobic after immersion in pH=2 and pH=12 for 48 hours).

Claims

1. A method for preparing a wear-resistant superhydrophobic coating with a dual covalently bonded interface, characterized in that, Includes the following steps: (1) Deionized water, ammonia and halloysite were added to anhydrous ethanol in sequence and stirred continuously under water bath conditions. Then tetraethoxysilane was slowly added dropwise while stirring at high speed to generate nano silica particles on the surface of halloysite in situ, forming HNTs-SiO2 micro-nano particles. (2) Slowly add a low surface energy substance to the mixed solution after generating micro-nano particles in step (1), and continue stirring in a water bath to obtain a superhydrophobic suspension; collect the precipitate after solid-liquid separation, and then dry, grind and sieve to obtain superhydrophobic composite particles. (3) Disperse the waterborne polyurethane resin and the superhydrophobic composite particles from step (2) in deionized water containing a nonionic surfactant. After mixing evenly, a coating is obtained. The coating is sprayed onto the substrate surface and cured to obtain a wear-resistant superhydrophobic coating.

2. The preparation method according to claim 1, characterized in that: In step (1), the halloysite has a hollow tubular structure with a pore size of 15-20 nm and a tube length of 5-20 μm; the silica nanoparticles on the surface of the halloysite have a particle size of 100-200 nm.

3. The preparation method according to claim 1, characterized in that: In step (1), the mass ratio of halloysite to tetraethyl orthosilicate is 6:5; the water bath reaction temperature is 45-55℃, and the reaction time is 6-8h.

4. The preparation method according to claim 1, characterized in that: In step (2), the low surface energy material is one of perfluorodecyltriethoxysilane, perfluorooctyltriethoxysilane or perfluorodecyltrichlorosilane; the amount of low surface energy material added is 16-17% of the amount of halloysite added.

5. The preparation method according to claim 1, characterized in that: In step (2), the water bath reaction temperature is 45-55℃ and the reaction time is 6-8h.

6. The preparation method according to claim 1, characterized in that: In step (3), the mass ratio of superhydrophobic composite particles to waterborne polyurethane resin is 1.5 to 3.5:

5.

7. The preparation method according to claim 1, characterized in that: In step (3), the deionized water contains 0.1% to 0.3% of a nonionic surfactant by mass.

8. The preparation method according to claim 7, characterized in that: The nonionic surfactant is selected from at least one of the following: alkylphenol polyoxyethylene ether nonionic surfactants, fatty alcohol polyoxyethylene ether nonionic surfactants, polyoxyethylene sorbitan ester nonionic surfactants, polyoxyethylene alkyl ether nonionic surfactants, and polyoxypropylene-polyoxyethylene block copolymer nonionic surfactants.

9. The preparation method according to claim 1, characterized in that: In step (3), the coating is sprayed onto the substrate surface on a hot plate at 120℃~170℃; the curing temperature is 100~150℃ and the curing time is not less than 4h.

10. The preparation method according to claim 1, characterized in that: In step (3), the thickness of the wear-resistant superhydrophobic coating is 10–80 μm.

Citation Information

Cited By

  • Photo-thermal super-hydrophobic anti-icing and deicing coating with excellent durability and preparation method thereof

    CN121649111A